Sociology in Germany. A History (excerpt) - Stephan Moebius (Journal of Economic Sociology, 2025)
The book presented by Professor Moebius is dedicated to the history of sociology in Germany from the late 19th century to the present day. It reflects on the era of the German Empire, the processes of institutionalization during the Weimar Republic, and the profound rupture caused by National Socialism; however, the author primarily focuses on the period after 1945. The book examines intellectual, institutional, and conflictual directions and trends in the history of German sociology within economic, political, social, and cultural contexts. Since the mid-1990s, theories and research projects aimed at studying social alienation, temporary or precarious employment, and xenophobia have gained prominence in sociological thought. Additionally, there has been a significant increase in gender studies and various fields of cultural studies. The landscape of sociological theories in Germany has evolved: whereas grand theories once dominated, there is now a trend toward rapidly changing sociological diagnoses of contemporary society. Professor Moebius raises questions about how these contemporary trends relate to the history of sociology. What is the purpose of this discipline? According to his perspective, the history of sociology is significant because it reflects society and analyzes its professional self-descriptions. Sociology is essential as it examines social effects and their consequences, as well as related ideological perspectives, struggles, and antagonistic power relations within the sociological field. The sociological analysis of sociology’s history reveals the dynamics of social phenomena within the science of society, thereby enhancing orderliness, self-reflection, and clarity within this discipline. The “Journal of Economic Sociology” publishes a brief excerpt titled “(Contemporary Trends and Discussions” from the book.